A Prospective Study on Screening of Congenital Heart Diseases using combined Pulse Oximetry and Clinical Examination in Neonates - DR SURESH KUMAR PANUGANTI; Bushigampula Bharath Kumar; Sudha Boda (Pediatric Review: International Journal of Pediatric Research, 2024)
Background: Congenital malformations are responsible for half of infant deaths, with congenital heart disease accounting for 10% of the fatalities. Clinical examination remains the primary method for diagnosing congenital heart disease in newborns.Materials and Methods: The study was conducted in the postnatal ward involving 224 newborns. Asymptomatic term newborns underwent screening for cyanotic congenital heart disease using pulse oximetry and clinical examination. The pulse oximetry was performed using a GE MONITOR device.Results:  Pulse oximetry saturation levels were below 90% in 5.4%, between 91-94% in 2.2%, and above or equal to 95% in 92.4% of the newborns.  The diagnoses included TOF (1; 0.5%), pulmonary stenosis (1; 0.5%), and tricuspid atresia (1; 0.5%). Among the newborns with positive pulse oximetry screening (oxygen saturation <95%), 17 were identified. Out of these, 3 had confirmed cyanotic congenital heart disease by echocardiography. Similarly, among the newborns with negative clinical examination screening (oxygen saturation ≥95%), 209 were identified. Out of these, 15 had positive clinical examination results, with 3 having confirmed cyanotic congenital heart disease by echocardiography.Conclusion: Pulse oximetry is a valuable screening tool for the early detection of congenital heart diseases, particularly cyanotic congenital heart diseases. It emphasizes the importance of both pulse oximetry and clinical examination results for a comprehensive screening approach. The study highlights the need for further research to refine and optimize the screening process for congenital heart diseases.